2017
DOI: 10.1016/j.aju.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Does sacral pulsed electromagnetic field therapy have a better effect than transcutaneous electrical nerve stimulation in patients with neurogenic overactive bladder?

Abstract: ObjectiveTo compare the effectiveness of pulsed electromagnetic field therapy (PEMFT) and transcutaneous electrical nerve stimulation (TENS) on neurogenic overactive bladder dysfunction (OAB) in patients with spinal cord injury (SCI).Patients and methodsIn all, 80 patients [50 men and 30 women, with a mean (SD) age of 40.15 (8.76) years] with neurogenic OAB secondary to suprasacral SCI were included. They underwent urodynamic studies (UDS) before and after treatment. Patients were divided into two equal groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…One study by Reilly showed that there was no significant difference between the MS therapy and sham intervention with regard to MVV, number of voids per day, pad test, VAS, and KHQ score. In the trials by Fergany et al comparing MS therapy and TENS intervention in patients with OAB symptoms, there was a significant improvement in MCC, first uninhibited detrusor contraction, and maximum urinary flow rate after treatment ( P = 0.001, P = 0.002, and P = 0.021, respectively).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…One study by Reilly showed that there was no significant difference between the MS therapy and sham intervention with regard to MVV, number of voids per day, pad test, VAS, and KHQ score. In the trials by Fergany et al comparing MS therapy and TENS intervention in patients with OAB symptoms, there was a significant improvement in MCC, first uninhibited detrusor contraction, and maximum urinary flow rate after treatment ( P = 0.001, P = 0.002, and P = 0.021, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Yamanishi et al compared MS with FES, Fergany et al compared MS with TENS, and remaining studies compared MS with sham. One study did not document the treatment of sham device, two studies used the 20.4% of active stimulation, two studies utilized the sham stimulating coil as the experimental group, one study applied 1 Hz as the sham stimulation, one study performed the sham stimulation with a thin deflective aluminium plate inserted in the chair, and remaining studies adopted stimulation with inactive device as the experimental group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations